Galeri Kesenian Anak Berkebutuhan Khusus TUNDAKAURU di Surakarta(Dengan Konsep Arsitektur Modern ) - Sari, Galuh Marita; , Dr. Ir. Dhani Mutiari, MT (2016)
Gallery is a place to appreciate the work of someone and accommodate the works of the artists and the interaction between the artist and his work with the community. Generally the gallery for a person with normal conditions on the gallery designed this time by standard aksesibelitas Children with Special Needs and the theme Acsesibel to all for the building of this gallery is designed as best as possible and have a sense of comfort, safe for users as well as art objects therein. The Role of Art Galleries for Children with special needs is to provide a container for more berkresasi khususagar needs children. Target Designing Art Gallery as containers or facilities for children with special needs in order to express their talent in accordance with the appropriate standards of accessibility and comfort with the concept of modern architecture in Surakarta,